2020
DOI: 10.3390/geosciences10020073
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic Review of Fossil Coleopterous Families (Insecta, Coleoptera). Suborder Archostemata: Superfamilies Coleopseoidea and Cupedoidea

Abstract: The paper is the first of a series, which aims to present a consistent interpretation of the suprageneric taxa of fossil beetles in the current century and their generic and species composition. Order Coleoptera is considered in composition of the superorder Coleopteroidea Handlirsch, 1903 (= Coleopterida sensu Boudreaux, 1979, nec Pearse, 1936 together with orders Skleroptera and Strepsiptera, and also with the family Umenocoleidae of unclear position. This paper includes the archostematan superfamilies Coleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
51
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 84 publications
0
51
1
Order By: Relevance
“…Ommatidae is a small family in the beetle suborder Archostemata, with only three extant genera, Omma Newman and Beutelius Escalona et al in Australia, and Tetraphalerus Waterhouse in South America (Hörnschemeyer & Beutel, 2016;Lawrence & Escalona, 2019;Escalona et al, 2020). Fossil records have revealed that ommatids had a much higher diversity during the Mesozoic, as well as wider distribution (Cai & Huang, 2017;Kirejtshuk, 2020). Morphologically, Ommatidae is most similar to the family Cupedidae.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ommatidae is a small family in the beetle suborder Archostemata, with only three extant genera, Omma Newman and Beutelius Escalona et al in Australia, and Tetraphalerus Waterhouse in South America (Hörnschemeyer & Beutel, 2016;Lawrence & Escalona, 2019;Escalona et al, 2020). Fossil records have revealed that ommatids had a much higher diversity during the Mesozoic, as well as wider distribution (Cai & Huang, 2017;Kirejtshuk, 2020). Morphologically, Ommatidae is most similar to the family Cupedidae.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, Mesozoic ommatids are only represented by compression or impression fossils, in which detailed structures are not well preserved. Recently, various exquisitely preserved ommatids have been described from mid-Cretaceous Burmese amber, including at least 21 species in 11 genera (generic assignment according to original authors) (Ross, , 2020Jarzembowski et al, 2020;Kirejtshuk, 2020). These amber inclusions with astonishingly fine details greatly enhanced our understanding of the diversity and disparity of Mesozoic ommatids.…”
Section: Introductionmentioning
confidence: 99%
“…Literature. Westwood (1854: 387/393) [ 109 ], Giebel (1856: 92) [ 85 ], Scudder (1885: 797) [ 105 ], Scudder (1886: 77) [ 106 ], Scudder (1891: 518) [ 34 ], Handlirsch (1906: 553) [ 35 ], Handlirsch (1907: 748) [ 93 ], Hyslop (1921: 644) [ 36 ], Dunstan (1923: 46) [ 100 ], Cockerell (1920: 456) [ 107 ], Handlirsch (1938: 14) [ 101 ], Jell (2004: 76) [ 102 ], Coram & Jepson (2012: 60) [ 110 ], Kirejtshuk (2020: 18) [ 111 ].…”
Section: Resultsmentioning
confidence: 99%
“…The importance of reconstructions and reviews of the fossil record for different coleopterous groups (for archostematans: see [9][10][11]-see also the references in the contribution by A.G. Kirejtshuk [12] in this issue) scarcely can be overestimated as opposed to the essentially incomplete of these versions of the fossil record. The suborder Archostemata seems to be the oldest and most basal one and knowledge of it therefore has a particular importance for modeling phylogenetic relationships.…”
mentioning
confidence: 99%
“…It could also be very valuable to prepare reviews of the fossil record for other large groups (as many as possible), which will make it feasible to propose such models with a better foundation. The contribution to archostematans included in this issue [12], is the first of a series of reviews of the suprageneric taxa of fossil beetles in the current century and their generic and species composition. The necessity of such reviews exists because different researchers have different experiences in the study of fossils, and the absence of such generalizations can create situations when misunderstanding appear between specialists and lead to confusions in interpretations.…”
mentioning
confidence: 99%